Determination method of silicites (siliceous raw materials): An explanation based on four selected raw materials. (30th March 2022) - Affolter, Jehanne; Wehren, Helena; Emmenegger, Lea
Abstract: Various methods exist to identify the source of siliceous materials used in prehistory. The only efficient and truly non-destructive method for archaeological objects exploits the fact that the majority of these silicifications derive from sedimentary formations. Sediments reflect the biotopes in which they formed, and each biotope differs from the others. Indeed, environmental conditions are never exactly the same. Reconstituting the depositional environment of a silicite bearing sediment allows us to deduce the place of its origin in an area with known geology, even if we do not know if there are flint outcrops. To demonstrate the used analytical approach for determination of the silicite resources, this article discusses four raw materials used in different Neolithic settlements during the 4th millennium BC in Switzerland.